Gadolinium Deposition in Humans: When Did We Learn That Gadolinium Was Deposited In Vivo?. Issue 4 (April 2016) - Huckle, James E.; Altun, Ersan; Jay, Michael; Semelka, Richard C.
Abstract : Abstract: Recently, there have been numerous major peer-reviewed publications reporting deposition of gadolinium in the dentate nucleus and globus pallidus in subjects with normal renal function. This review takes a retrospective look back through the development of gadolinium-based contrast agents to describe the historical evidence of gadolinium deposition in vivo and shows that deposition in the basal ganglia should come as no surprise. Evidence for gadolinium deposition in both animal models and human patients is described. Stability differences among gadolinium contrast agents have long been recognized in vitro, and deposition of gadolinium in tissues has been described in animal models since at least 1984. The first major study that showed deposition in humans appeared in 1998 regarding patients with renal failure and in 2004 in patients with normal renal function. The historical literature indicates that gadolinium retention in healthy patients is occurring, although the clinical consequences of deposition remain unknown.